THE INFLUENCE OF SCHOOL SPORTS EQUIPMENT IN THE QUALITY OF SPORTS DEVELOPMENT IN RIO DE JANEIRO (Fiep Bulletin - online, 2011)
The article promotes a comparative analysis between the Sports Development Index (SDI), and the Sports Development Index of the City (SDIC), which are born from a methodology described by Kubrusly (2001) as a selection of variables, showing that the level of sports development in a specific area is related to the schools' sports equipment. The article concludes that the school space gets the opportunity to be, contrary to those that are dedicated to more critical and less simplistic interpretations about reality, an urban persona that redeems society's problems and, in this perspective, one of the most important factors for the economic, cultural, political, social and sports development in a city.
Keywords: School sports equipments; Sports Development Index